(untitled) (International Seven Journal of Health Research, 2023)
During a four-month period (January to April) in the year 2023, a significant increase in the prescription of benzodiazepines was observed in the family health strategy (ESF). This increase covered patients of different age groups, with emphasis on high consumption among young adults and the elderly. The area served by the FHS has a high social vulnerability, with several families with a history of suicide and drug and alcohol users, which may be related to the indiscriminate use of benzodiazepines. The objective of this study is to analyze alternatives for weaning from benzodiazepines, using illustrative instruments and conversation circles as support. This experience report describes the implementation in individual medical consultations, the use of illustrative tables and suggestions for conversation circles in the community. Medical consultations followed the conceptual model of the person-centered clinical method, using communication skills and promoting knowledge building through conversation circles. Illustrated tables presenting the weaning weeks, the mode of use and the formulation of benzodiazepines were used, as well as a folder with guidelines on sleep hygiene. The use of these illustrated tables proved to be satisfactory, with greater adherence on the part of the elderly, and provided a greater bond between the health professional and the patient, allowing to know the patient’s experiences in relation to the treatment and their disease.